2013
DOI: 10.1038/jcbfm.2013.194
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reactivity in the Brain White Matter: Magnitude, Temporal Characteristics, and Age Effects

Abstract: White matter (WM) comprises about half of the brain and its dysfunction is implicated in many brain disorders. While structural properties in healthy and diseased WM have been extensively studied, relatively little is known about the physiology underlying these structural characteristics. Recent advances in magnetic resonance (MR) technologies provided new opportunities to better understand perfusion and microvasculature in the WM. Here, we aim to evaluate vasodilatory capacity of the WM vasculature, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
99
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 40 publications
18
99
0
1
Order By: Relevance
“…However, we did not use the frequency spectrum-based technique for response delay estimation, as low-frequency physiological noise interfered within the frequency bandwidth of our stimulus. Rather, our delay-estimation method is similar to that of Thomas et al (2014). Nonetheless, our findings of earlier response in the frontal lobe and later response in the occipital lobe as well as the subcortical gray matter structures are in agreement with previous findings (Blockley et al, 2011;Bright et al, 2009).…”
Section: The Effect Of Baseline Vascular Tension On Co 2 Response Delaysupporting
confidence: 82%
“…However, we did not use the frequency spectrum-based technique for response delay estimation, as low-frequency physiological noise interfered within the frequency bandwidth of our stimulus. Rather, our delay-estimation method is similar to that of Thomas et al (2014). Nonetheless, our findings of earlier response in the frontal lobe and later response in the occipital lobe as well as the subcortical gray matter structures are in agreement with previous findings (Blockley et al, 2011;Bright et al, 2009).…”
Section: The Effect Of Baseline Vascular Tension On Co 2 Response Delaysupporting
confidence: 82%
“…4C), and that of others (Reich and Rusinek, 1989). It may also help explain or interpret elevated WM BOLD-CVR (Thomas et al, 2014) and CBF (Lu et al, 2011) with increasing age that have been reported elsewhere.…”
Section: Age-dependent Changes In Cbf Distributionmentioning
confidence: 73%
“…Age, blood pressure and gender are in themselves thought to alter CVR 17,21 and therefore may have affected the results. Even where these variables were reported, the studies varied as to whether they corrected for these factors when assessing CVR.…”
Section: Discussionmentioning
confidence: 99%
“…There is known to be a significant delay between change in EtCO 2 and change in BOLD signal in the white matter compared to the grey matter. 21,28 It is therefore vital that the different delay between brain structures is taken into account during analysis and that the period of hypercapnia is long enough for all tissues to achieve a representative change in BOLD signal. The delay itself may be an important part of the assessment of CVR.…”
Section: Discussionmentioning
confidence: 99%